2017
DOI: 10.1002/rmb2.12021
|View full text |Cite
|
Sign up to set email alerts
|

Protein biomarkers for male artificial insemination subfertility in bovine spermatozoa

Abstract: BackgroundAlthough artificial insemination (AI) technique is an established biotechnology for bovine reproduction, the results of AI (conception rates) have a tendency to decline gradually. To our annoyance, moreover, AI‐subfertile bulls have been occasionally found in the AI centers. To resolve these serious problems, it is necessary to control the sperm quality more strictly by the examinations of sperm molecules.MethodsWe reviewed a number of recent articles regarding potentials of bovine sperm proteins as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 110 publications
(162 reference statements)
0
19
0
Order By: Relevance
“…Several studies have shown that the characteristics of sperm quality, such as motility, capacitation, and morphology, affect conception in cattle [4, 29,30,31,32]. However, to our knowledge, there are few studies showing that only improving bovine sperm quality could lead to beneficial effects on fertilization or embryo development.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that the characteristics of sperm quality, such as motility, capacitation, and morphology, affect conception in cattle [4, 29,30,31,32]. However, to our knowledge, there are few studies showing that only improving bovine sperm quality could lead to beneficial effects on fertilization or embryo development.…”
Section: Discussionmentioning
confidence: 99%
“…1,16,23,24 Thus, it is necessary to make detailed researches on the interspecies differences in the sperm functions in order to elucidate mechanisms for the expression of fertilizing ability in mammalian spermatozoa. According to our previous investigations of bull and boar spermatozoa, [25][26][27][28][29] and PKA are localized in the specific subcellular segments including the connecting and principal pieces, and proteins are preferentially phosphorylated in these segments of the spermatozoa treated with the cAMP analog to induce capacitation-related events leading to hyperactivation. These results are consistent with our hypothesis that connecting pieces of bull and boar spermatozoa have unique cAMP-dependent controllers for regulation of the capacitation-related events leading to hyperactivation.…”
mentioning
confidence: 99%
“…Furthermore, in the examination for the selection of lot numbers of straws of frozen spermatozoa, some of the testing straws are thawed and subjected to the evaluation of sperm motility. Thereafter, the remaining straws with the same lot numbers as the testing straws that have passed the examination of sperm motility are used for AI [ 1 , 2 ]. Motility of the spermatozoa is one of the most important characteristics associated with their fertilizing ability.…”
mentioning
confidence: 99%